Classification and Procedure of Business Product Innovation - Pipit Primadhani; Dwi Susilawati (Enigma Institute, 2023)
Product innovation encompasses the generation of novel concepts, modifications, and enhancements to current offerings with the aim of more effectively satisfying client demands and potentially forging new market opportunities. The range of product innovation in a business environment is highly varied and can serve as the primary catalyst for enhancing a company's competitiveness in this dynamic period. Every category of innovation plays a distinct role and has a specific impact on addressing company challenges and possibilities. Companies that integrate many forms of innovation in alignment with their strategy and business objectives will enhance their ability to sustain competitiveness and effectively navigate market fluctuations. Through the implementation of appropriate product innovations, organizations can enhance their market presence, augment client contentment, and attain sustainable expansion.